History of Maryamah Town (Hajar- al- ‘Adī) in Wādī Ḥarīb in the Light of its Musnad Inscriptions (7th Century BC – 3rd Century AD) - Alhajj, Mohammed Ali (مركز عبد الرحمن السديري الثقافى, 2019)
This study aims at shedding light on the history of a significant Qatabanian town which was known as Maryamah, in Wadi Ḥarib, in the light of its Musnad Inscriptions during the period from the 7th century BC to 3rd century AD. It presents some important historical data about a Qatabanian town that had not been known earlier, and which had a vital role in the history of Ancient Yemen. This is the first research that tries to discuss the history of Maryamah town. In fact, there had been no studies on any aspect of such a town regarding its chronological order, according to its inscription data, except a few previous studies the researcher conducted in Arabic. The study is mainly based on Qatabanian inscriptions which the researcher has collected from Maryamah during the past few years. They reached so far 120 Qatabanian inscriptions that were dedicatory, construction, legislative, and memorial inscriptions, as well as other Qatabanian inscriptions which had been published and smuggled to Arabian and foreign museums, and those preserved by private groups.
Keywords: النقوش التاريخية -- النقوش القتبانية -- مريمة